Landslide Risk Analysis using a New Constitutive Relationship for Granular Flow - Ren, Diandong; Leslie, L.; Karoly, D. (American Geophysical Union, 2008)
In this study, landslide potential is investigated, using a new constitutive relationship for granular flow in a numerical model. Unique to this study is an original relationship between soil moisture and the inertial number for soil particles. This numerical model can be applied to arbitrary soil slab profile configurations and to the analysis of natural disasters, such as mudslides, glacier creeping, avalanches, landslips, and other pyroclastic flows. Here the focus is on mudslides.The authors examine the effects of bed slope and soil slab thickness, soil layered profile configuration, soil moisture content, basal sliding, and the growth of vegetation, and show that increased soil moisture enhances instability primarily by decreasing soil strength, together with increasing loading. Moreover, clay soils generally require a smaller relative saturation than sandy soils for sliding to commence. For a stable configuration, such as a small slope and/or dry soil, the basal sliding is absorbed if the perturbation magnitude is small. However, large perturbations can trigger significant-scale mudslides by liquefying the soil slab.The role of vegetation depends on the wet soil thickness and the spacing between vegetation roots. The thinner the saturated soil layer, the slower the flow, giving the vegetation additional time to extract soil moisture and slow down the flow. By analyzing the effect of the root system on the stress distribution, it is shown that closer tree spacing increases the drag effects on the velocity field, provided that the root system is deeper than the shearing zone.Finally, the authors investigated a two-layer soil profile, namely, sand above clay. A significant stress jump occurs at the interface of the two media.